The Neuroendocrine Secretion Regulates Growth Hormone Release in Teleost Fish - Phale, Sameer R. (Fishery Technology, 2025)
The growth hormone (GH) secretion in cyprinids and other teleost species is apparently regulated by several neuroendocrine factors working together. Somatostatin is the primary inhibitor of basal and stimulated GH release while the other inhibitors are norepinephrine and serotonin. The GH secretion is stimulated by GH- releasing hormone, gonadotropin-releasing hormone, thyrotropin-releasing hormone, cholecystokinin, bombesin, neuropeptide Y, dopamine and galanin. The growth rate of cultured fish may be stimulated by neuroendocrine factors added to food, or by administration of GH or recombinant GH preparations. Techniques for enhancing growth rates of cultured fish are in an experimental stage.